Limitation of Claims in Polish and Ukrainian Civil Code against the Background of the Principles of European Contract Law and the German Civil Code - Buletsa, Sibilla; Zakrzewski, Piotr (Journal of Legal Studies, 2019)
The article deals with limitation of claims in Poland, Ukraine and Germany. The authors made a conclusion that the most liberal solution in the area of contractual regulation of limitation is provided in the German Civil Code, which allows shortening and prolonging the statutory limitation period, whereas the most severe is provided for in the Polish Civil Code, prohibiting it altogether. An indirect solution has been adopted by the Ukrainian Civil Code, which allows only the extension of the statutory limitation period. These different legislative solutions demonstrate that the national legislators are partially different in their view of the reasons justifying the statute of limitations. Newer prescription regulations, to which the German and Ukrainian ones belong, are largely similar to each other. The same can be said about the Polish academic project of the general section of the civil code. The Principles of European Contract Law have had a significant impact on teaching of civil law, as well as on national legislators.